Celebrity-in-chief how show business took over the White House - Schroeder, Alan 1954-
U.S. presidents and Hollywood have had a mutual admiration society that extends far back into history. In Celebrity-in-Chief, journalist Alan Schroeder contends that each camp has influenced the other-particularly over the past century-creating a president who no longer stands apart upon a remote civic pedestal, isolated from Hollywood and pop culture. Instead, the powerful forces of the American celebrity circus drag him into the tent and ask him to put on a show. The job of president has always been politically demanding, but now there is another requirement: to exude star quality. In the parlance of Hollywood, he must "fill the frame." Drawing upon a wealth of fascinating anecdotes about some of the most celebrated individuals in American history, Schroeder shows how a succession of presidents since Woodrow Wilson has put on a show with mixed results. Whether it was Bill Clinton playing sax on TV talk shows or George W. Bush's Top Gun stunt aboard an aircraft carrier, Celebrity-in-Chief entertainingly and convincingly shows that the result is a wholesale demystification of the office-and that this marriage of pop culture and the presidency will continue to fascinate and endure.